2007
DOI: 10.1186/gb-2007-8-2-r27
|View full text |Cite
|
Sign up to set email alerts
|

microRNA expression in the prefrontal cortex of individuals with schizophrenia and schizoaffective disorder

Abstract: Background: microRNAs (miRNAs) are small, noncoding RNA molecules that are now thought to regulate the expression of many mRNAs. They have been implicated in the etiology of a variety of complex diseases, including Tourette's syndrome, Fragile × syndrome, and several types of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
438
1
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 504 publications
(461 citation statements)
references
References 55 publications
18
438
1
4
Order By: Relevance
“…Among the differentially expressed miRNAs in our study, miR‐212‐5p has been shown to be downregulated in patients with ASD and schizophrenia 9, 36. Reduced expression of miR‐212 and miR‐132 was also observed in human Alzheimer's disease brains 37.…”
Section: Discussionsupporting
confidence: 53%
“…Among the differentially expressed miRNAs in our study, miR‐212‐5p has been shown to be downregulated in patients with ASD and schizophrenia 9, 36. Reduced expression of miR‐212 and miR‐132 was also observed in human Alzheimer's disease brains 37.…”
Section: Discussionsupporting
confidence: 53%
“…Therefore the authors hypothesized that the downregulation of miRNAs they observed is due to altered miRNA biogenesis rather than altered transcription of primiRNA. This is in keeping with the speculation that the potential involvement of the DiGeorge critical region gene 8 encoded protein (an RNA-binding protein that assists Drosha in the processing of miRNAs) in schizophrenia is via its regulation of miRNA biogenesis [63].…”
Section: Mirna and Human Diseasessupporting
confidence: 78%
“…By using microarrays spotted with probes against 265 human miRNAs (at a false discovery rate of 5%), the authors found 16 miRNAs to be differentially expressed: 15 showed decreased expression and one showed higher expression in the schizophrenia patients as compared with controls. For miRNAs residing in introns of protein-coding genes, they observed that the ratios of microarray expression levels of miRNA versus mRNA (of the respective host gene) were significantly different for four of the six hosted miRNAs distinguished by schizo-phrenia [63]. Therefore the authors hypothesized that the downregulation of miRNAs they observed is due to altered miRNA biogenesis rather than altered transcription of primiRNA.…”
Section: Mirna and Human Diseasesmentioning
confidence: 95%
See 1 more Smart Citation
“…MiR-9 and miR-128a were overexpressed in the brains of Alzheimer's patients and 16 miRNAs were differentially expressed in the brains of schizophrenics. A mutation in the 3' UTR of the SLITRK1 gene that is associated with Tourette's syndrome led to enhanced repression by miR-189 [84][85][86][87]. Several hundreds of miRNAs were identified in human but currently, only a couple of specific targets have been experimentally validated.…”
Section: Mirnas-associated Disease Mechanismsmentioning
confidence: 99%